Bumbung Gelombang Lingkaran Susun Untuk Aplikasi RF Energy Harvesting pada GSM 1800 MHz - Praja, Muhammad Panji (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2021)
Mobile device for mobile communication, especially GSM communication is one of the most important thing in our daily activities. A massive mobilty and connectivity to make sure everyone is connected to each other is necessary. In a same time, electrical power needs will increase in order to support the increasingly rapid exchange of information. In this research shown the result of circular waveguide array mode TM01 measurement for RF energy harvesting application at frequency GSM 1800 MHz â€“ 1900 MHz. Design of circular waveguide array through parameter study developed an optimum result, return loss Â at frequency centre 1850 MHz. Realization of this design is measured in unechoic chamber for minimizing a reflected wave from the ambient, so it called an ideal area for waveguide parameter measurement. The measurement results return loss at freuquency 1840 MHz